Referral and Final Diagnoses of Patients Assessed in an Academic Vertigo Center - Geser, Rebekka; Straumann, Dominik (Frontiers in Neurology, 2012)
OBJECTIVE: To identify under-diagnosed neuro-otological disorders and to evaluate whether under-diagnosing depends on the age of the patient. MATERIAL AND METHODS: Retrospective analysis of medical charts from 951 consecutive patients (685 under and 266 above the age of 65 years) who entered diagnostic procedures at the Interdisciplinary Center for Vertigo and Balance Disorders, University Hospital Zurich, Switzerland. Final diagnoses were compared to referral diagnoses. RESULTS: Relative to referral diagnoses, the proportion of patients finally diagnosed with benign paroxysmal positional vertigo (BPPV) almost doubled both in younger (< 65 year from 12.7% to 25.1%) and older patients (from 20.7% to 37.6%). Striking relative increases were found for the diagnoses multisensory dizziness in older patients (from 20.7% to 37.6%) and vestibular migraine in younger patients (1.8% to 20.2%). In both age groups, the proportion of patients with undetermined diagnoses was reduced by about 60% (younger: 69.8% to 9.8%; older: 69.2% to 12.4%) by the diagnostic procedures in the vertigo center. These changes were all significant (p < 0.05) in McNemar tests with continuity correction (2x2 tables: focused diagnosis vs. other diagnoses, referral vs. final). CONCLUSION: Significant changes of diagnoses can be expected by a specialized neuro-otological work-up. In particular, BPPV, multisensory dizziness, and vestibular migraine are under-diagnosed by referring physicians. This finding calls for better education of primary care takers in the field of neuro-otology.